Resilient employees are creative employees, when the workplace forces them to be - De Clercq, Dirk (2020)
With a basis in conservation of resources theory, this article considers the connection between employees' resilience and disruptive creative behaviour—conceptualized herein as the extent to which they generate radically new ideas for organizational improvement—as well as how this connection might be invigorated by resource‐draining work conditions that stem from excessive workloads and unfavourable decision‐making processes. Data collected through a survey administered to employees in an organization that operates in the distribution sector reveal that employees' resilience levels spur their disruptive creative behaviour, and this process is more prominent among employees who believe they have insufficient time to complete their work tasks (i.e., suffer from high work overload) and operate in organizational climates marked by high rigidity or dysfunctional politics. The findings accordingly inform organizational practitioners that the allocation of employees' personal resource bases to disruptive creative behaviours might be particularly useful among employees who face substantial adversity in their organizational functioning.